A new colorimetric peptide nucleic acid-based assay for the specific detection of bacteria - Almeida, Carina (2014)
Aim: Developments on synthetic molecules, such as peptide nucleic acid (PNA), make FISH procedures more robust for microbial identification. Fluorochromes use might hinder a broader implementation of PNA-FISH, but colorimetric applications are inexistent so far. Methods: A biotin-labeled eubacteria probe was used to develop a colorimetric PNA-in situ hybridization (ISH) assay. An enzymatic-conjugate, targeting biotin, was introduced. The procedure was optimized and evaluated regarding sensitivity, specificity and detection limit. Results: Results have shown strong ISH signals. The method was specific, but permeabilization problems were observed for Gram-positive bacteria. Detection limit was 5 × 107 CFU/ml, limiting current applications to pre-enriched samples. Conclusion: The PNA-ISH procedure described here is a simple alternative to other detection methods, and is also the base for the development of other PNA colorimetric systems.